2017
DOI: 10.1039/c6rp00240d
|View full text |Cite
|
Sign up to set email alerts
|

The effect that comparing molecular animations of varying accuracy has on students’ submicroscopic explanations

Abstract: In this qualitative study, we examined how a group of seventeen first semester General Chemistry students responded when they were shown contrasting molecular animations of a reduction–oxidation (redox) reaction between solid copper and aqueous silver nitrate for which they first viewed a video of the actual experiment. The animations contrasted in that they portrayed different reaction mechanisms for the redox reaction. One animation was scientifically accurate and reflected an electron exchange mechanism, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 16 publications
2
26
0
5
Order By: Relevance
“…Tarkin and Uzuntiryaki-Kondakci (2017) reported that students had difficulty applying their theoretical knowledge about oxidationreduction concepts when interpreting daily life events. Cole et al (2019), Haigh et al (2012), Kelly et al (2017) and Testa et al (2018) identified that students were not able to correctly correlate the color change with the oxidation / reduction of the substance. In addition, many students were unable to identify the source of the color change in solution.…”
Section: Limitations Of Teaching and Learning Redox Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tarkin and Uzuntiryaki-Kondakci (2017) reported that students had difficulty applying their theoretical knowledge about oxidationreduction concepts when interpreting daily life events. Cole et al (2019), Haigh et al (2012), Kelly et al (2017) and Testa et al (2018) identified that students were not able to correctly correlate the color change with the oxidation / reduction of the substance. In addition, many students were unable to identify the source of the color change in solution.…”
Section: Limitations Of Teaching and Learning Redox Reactionsmentioning
confidence: 99%
“…Cole et al (2019);Haigh et al (2012);Kelly et al (2017);Koenig et al (2019);Llanos et al (2019);Lee (2007);Niaz and Chacón (2003);Tarkin and Uzuntiryaki-Kondakci (2017); Testa et al(2018);Yang et al (2004);Yang et al (2003).Identifying the species that reduces and the species that oxidizes Acar and Tarhan (2007)Eybe and Schmidt (2001);Messersmith (2014);Niaz (2002);Niaz and Chacón (2003);Schmidt and Volke (2003); Schultz(2008); Supasorn (2015); Rosenthal and Sanger (2012).…”
mentioning
confidence: 99%
“…Além da transferência, outras dificuldades contribuem para que este conteúdo seja considerado de difícil compreensão pelos estudantes devido ao seu alto grau de abstração, como por exemplo, em relação aos seguintes conceitos: oxidação e redução, agente oxidante e redutor, números de oxidação, etc. (Akram, Surif & Ali, 2014;Freire, Junior & Silva, 2011;Goes, Fernandez & Agostinho, 2016;Kelly, Akaygun, Hansen & Cerdas, 2017;Dow, 2018, Klein & Braibante, 2017. A partir disso, percebe-se que vários são os fatores que corroboram para o surgimento dos diferentes obstáculos no processo de ensino e aprendizagem a respeito deste conteúdo, gerando cada vez menos indícios de aprendizagem significativa (na visão de Ausubel, 1982).…”
Section: Introductionunclassified
“…Recently, some researchers explored students’ understanding of redox reactions at the submicroscopic level as connected with the macroscopic level, involving students in a laboratory practicum, a demonstration of a redox reaction and an observation in a natural setting, making use of computer animations, or a redox concept inventory, which was developed based on information from student interviews . Österlund and Ekborg investigated students’ reasoning about redox reactions for three different situations.…”
Section: Introductionmentioning
confidence: 99%